Chapter II: the historical & cultural buildings / Wan Juliana Emeih Wahed and Clement Jimel - Emeih Wahed, Wan Juliana; Jimel, Clement (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
The Equator, holds a position of profound significance and intrigue. Being one of the few locations on Earth where this imaginary line intersects land, it presents a remarkable opportunity to witness and understand its associated phenomena. Standing at the Equator in Pontianak, one can observe the extraordinary spectacle of the sun being directly overhead at noon, not once but twice a year during the equinoxes. This rare celestial event, where no shadows are cast at precisely noon, captures the Earth's axial tilt and its impact on the distribution of sunlight. Beyond its scientific marvel, the Equator in Pontianak is the experiential act of standing in two hemispheres simultaneously becoming a memorable and reflective moment, embodying the tangible division of our planet. While exploring the Equator, one can engage in educational exhibits and interactive displays that delve into this geographical phenomenon's scientific principles and cultural significance. Gain insights into the equatorial climate's influence on the region's diverse flora and fauna, and discover how different cultures worldwide celebrate and honour the Equator.